Avaliação da qualidade da água do Rio Piranhas-Açu/RN utilizando a comunidade de macroinvertebrados bentônicos - Ottoni, Bianca Maíra de Paiva (2009)
The biomonitoring technique for water quality in water bodies has been incorporated increasingly in management of the natural resources, using mainly indices of its aquatic community characteristics. In Brazil the first efforts to use this technique was restricted to the South and the Midwest region of this country. Located in the northeast region, this study was conducted at Rio Grande do Norte state and had as main objective the assessment of water quality in the Piranhas-Açu river using benthic macroinvertebrates community as biological indicators. Thus, were applied two biotic indices, the BMWP (Biological Monitoring Working Party score system) and the IBF (Family Biotic Index). According the requirements of these indices, two periods of sampling were determined as basic methodology, in dry seasons of 2006 and 2007. The sampling sites were around the municipalities of Açu, Ipanguaçu, Alto do Rodrigues and Pendências. Physical-chemical measurements; a protocol of rapid assessment of diversity of habitats, and determination of the degree of tolerance of each taxon to organic pollution were also performed. The most abundant organisms found in the river were tolerant with the prevalence of Chironomidae (Diptera) and Melanoides tuberculata. This results, together with those ones got in indices application, showed a considerable organic pollution in the four sample places and the reaches were classified as modified to impacted. According to the used indices, this study suggest that this river have significant alteration in the biotic community and water quality on the organic pollution, and this fact, occurs in the reach of the river further downstream, where were expected a good water quality. Considering these results, measures aiming the conservation of this water body are needed regarding as it is inserted into a fragile ecosystem with dry season phenomenon, and the water of this river has extremely importance for the local economy